(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Bangladesh has an agrarian economy in which paddy is the dominant crop. A significant amount of field losses of paddy occurs every year due to natural calamities and a shortage of time during the harvesting period. During this study, a modification was done on locally developed BAU self-propelled reaper and its performance was compared with manual harvesting system of paddy. Several experiments were conducted in Boro paddy (April–May 2017) and Aman paddy harvesting (November–December 2017) at BAU farm of Bangladesh Agricultural University after necessary modification works in the workshop. An experiment was also conducted on Aman paddy in 2017 at BAU farm for determining manual harvesting cost. The technical and economic performances of the modified BAU self-propelled reaper were determined based on the field experiments. Results reveal that average fuel consumption, effective field capacity and field efficiency were 2.71 L/ha, 0.255 ha/h and 77.27%, respectively for the modified BAU self-propelled reaper and 2.88 L/ha, 0.25 ha/h and 75.76%, respectively for the existing BAU self-propelled reaper. These results indicated that field performances of modified BAU self-propelled reaper were better than that of the existing BAU reaper. Paddy harvesting cost was found 916 Tk/ha for modified BAU self-propelled reaper and 9200 Tk/ha for manual harvesting system. The benefit-cost ratio of the modified BAU self-propelled reaper was 2.18. Considering the technical and economic performances, modified BAU self-propelled reaper was found suitable than the existing BAU reaper. So, the modified BAU self-propelled reaper may be introduced in Bangladesh in the commercial basis. J. Bangladesh Agril. Univ. 16(2): 171-177, August 2018